2011
DOI: 10.1136/heartjnl-2011-300198.145
|View full text |Cite
|
Sign up to set email alerts
|

145 Characterisation of fractionated atrial electrograms critical for maintenance of AF: a randomised controlled trial of ablation strategies (the CFAE af trial)

Abstract: mice showed a significant reduction in the cardiomyocyte cross sectional area (sham, 26763.4 mm 2 , vehicle treated TAC mice, 48065.8 mm 2 , AP2 treated TAC mice, 31963.9 mm 2 ). A significant reduction in the expression of the hypertrophic marker ANP and BNP and in the percentage of fibrosis was also observed in these mice compared with vehicle treated TAC mice. AP2 treatment led to a significant reduction in the expression of the bona fide calcineurin target RCAN1.4 and a reduction in the NFAT phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Previous studies investigating the impact of PVI on mechanisms sustaining AF have used surrogates for drivers such as fractionated electrograms or dominant frequency. PVI has been shown to reduce dominant frequency 14 and the burden of fractionated electrograms 12‐14,17 . However, fractionated electrograms and peaks in dominant frequency correlate poorly with drivers in AF 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the impact of PVI on mechanisms sustaining AF have used surrogates for drivers such as fractionated electrograms or dominant frequency. PVI has been shown to reduce dominant frequency 14 and the burden of fractionated electrograms 12‐14,17 . However, fractionated electrograms and peaks in dominant frequency correlate poorly with drivers in AF 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Mapping studies have shown that the burden of fractionated electrograms, the cycle length (CL) of electrograms, and the dominant frequency of the atria are reduced following PVI which suggests an impact on mechanism sustaining AF in the body of the atria 12‐14 . Targeting of ganglionated plexi has been shown to eliminate areas of continuous fractionation, both locally and at distant sites, and, hence, damage to ganglionated plexi at the pulmonary vein (PV) ostia has been suggested as one potential mediator of wider spread changes in AF mechanisms 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient defragmentation at the RA, however, may reduce the critical mass necessary to maintain chronic biatrial AF, subsequently resulting in AF termination . Targeting certain CFAE in LA or RA may also eliminate focal drivers of AF . All these mechanisms may explain why aggressive substrate modification by ablation could not only increase the acute procedural successful rate but also improve the clinical outcome during follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…The LA was subdivided into anterior, posterior/inferior, lateral, roof, and septal regions. This was achieved through using a segmented model of the LA, which is a simplified version of a model previously published . The posterior wall was defined as the posterior aspect of the LA enclosed by the PVs.…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved through using a segmented model of the LA, which is a simplified version of a model previously published. 9 The posterior wall was defined as the posterior aspect of the LA enclosed by the PVs. The inferior wall was the area extending below the inferior PVs down to the mitral valve annulus inferiorly and enclosed by the inferior aspect of the septum and the lateral aspect of the LA.…”
Section: Atrial Coveragementioning
confidence: 99%